Flexible‐Device Injector with a Microflap Array for Subcutaneously Implanting Flexible Medical Electronics. Issue 15 (25th June 2018) - Song, Kwangsun; Kim, Juho; Cho, Sungbum; Kim, Namyun; Jung, Dongwuk; Choo, Hyuck; Lee, Jongho
Abstract: Implantable electronics in soft and flexible forms can reduce undesired outcomes such as irritations and chronic damages to surrounding biological tissues due to the improved mechanical compatibility with soft tissues. However, the same mechanical flexibility also makes it difficult to insert such implants through the skin because of reduced stiffness. In this paper, a flexible‐device injector that enables the subcutaneous implantation of flexible medical electronics is reported. The injector consists of a customized blade at the tip and a microflap array which holds the flexible implant while the injector penetrates through soft tissues. The microflap array eliminates the need of additional materials such as adhesives that require an extended period to release a flexible medical electronic implant from an injector inside the skin. The mechanical properties of the injection system during the insertion process are experimentally characterized, and the injection of a flexible optical pulse sensor and electrocardiogram sensor is successfully demonstrated in vivo in live pig animal models to establish the practical feasibility of the concept. Abstract : A flexible‐device injector that enables the subcutaneous implantation of flexible medical devices is proposed and validated with in vivo demonstrations for flexible physiological sensors including a photoplethysmographic pulse sensor and electrocardiogram sensor, in live pig animal models to prove the feasibility of the concept.